A low-cost multifunctional PBAT foaming modified material and preparation method thereof

By reacting with polyhydroxy sugars and using chain extenders and other technologies, the problems of poor melt strength and high cost of PBAT are solved, and the preparation of multifunctional low-cost PBAT foaming modified materials is realized, and its application in multiple fields has been expanded.

CN116478442BActive Publication Date: 2025-04-25CHANGLIAN LIGHT MATERIAL (NANJING) TECH CO LTD

Patent Information

Application Number
CN202310291420.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-22
Publication Date
2025-04-25
Estimated Expiration
2043-03-22

AI Technical Summary

Technical Problem

The low melt strength, high cost of biodegradable materials and poor functionalization of PBAT limit its wide application in high and low-end fields.

Method used

By reacting with low-cost polyhydroxy sugars and using chain extenders, compatibilizers, functional additives, etc. to perform chain expansion functionalization reaction with PBAT, a multifunctional low-cost PBAT foaming modified material is prepared, achieving cost reduction, melting and functional impartment.

Benefits of technology

It realizes low-cost and high-rate foaming of PBAT materials, imparts antibacterial, barrier, adsorption and other functions to the materials, and expands its application in food preservation, electronic packaging, medical care, shoe materials and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure HDA0004141679100000011
    Figure HDA0004141679100000011
Patent Text Reader

Abstract

The present invention relates to a low-cost multifunctional PBAT foaming modified material and a preparation method thereof. The present invention mainly aims at the poor melt strength of PBAT, the high cost of biodegradable materials and the poor functionalization. A preparation technology of a multifunctional low-cost PBAT foaming modified material is developed. Low-cost polyhydroxy sugars are used to react with functional groups, and chain extenders, compatibilizers, functional additives and the like are used to carry out chain extension functionalization reactions with PBAT. While achieving cost reduction and melting increase of PBAT, certain functional effects such as antibacterial, barrier and adsorption are also given to it. The ratio is adjustable between 2 and 30 times, and the opening and closing pores are adjustable, which promotes the application of biodegradable materials in the fields of food preservation, electronic packaging, medical treatment, shoe materials and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a low-cost multifunctional PBAT foaming modified material and a preparation method thereof, and mainly aims at the poor melt strength of PBAT, the high cost of biodegradable materials, and the poor functionality, and develops a preparation technology of a multifunctional low-cost PBAT foaming modified material. Background Art

[0002] With the international and domestic "plastic ban" and the demand for "carbon neutral" economic development, the polymer materials industry has set off a climax in the research and application of biodegradable materials. However, the high cost of biodegradable materials has limited their widespread promotion to a certain extent. Therefore, there is an urgent need for green, lightweight and cost-reduction technologies while ensuring their biodegradable properties.

[0003] At present, the main categories of biodegradable materials are PLA, PBAT, PBS, etc., among which PBAT has the lowest price. However, the current lightweight applications are mainly based on PLA materials, such as extruded foamed PLA and low-ratio PLA blister foam products, which are mostly used in low-end consumables such as lunch boxes and drinking cups. There are very few lightweight products made of low-cost PBAT materials, especially low-cost high-ratio foam products. These are mainly due to the low melt strength of PBAT. Therefore, it is urgent to develop a class of low-cost functional PBAT foaming materials to promote the low-cost application of biodegradable materials in high- and low-end fields.

[0004] Patent CN 113549305 A discloses a fully biodegradable modified PBAT foam sheet and its preparation method, which mainly uses PBAT and one of the rigid polymers of polylactic acid, low-density polyethylene LDPE, and polypropylene PP, and completes the melting and rigidification effect on the PBAT molecular structure by blending with epoxy chain extenders, and the mass ratio of the rigid polymer to PBAT is (5-30): 100. However, epoxy chain extenders mainly react violently with hydroxyl and carboxyl groups, and have limited reaction with CH bonds in polyethylene and polypropylene. In addition, LDPE and PP are completely non-degradable materials, and the high content also affects the fully biodegradable performance of the product to a certain extent. Blending and chain extension with PLA polymers can achieve rigidification to a certain extent, but the high molecular weight PLA has limited reaction rigidity on the PBAT molecular chain and is relatively expensive. Summary of the invention

[0005] The present invention relates to the field of foaming, and mainly aims at the poor melt strength of PBAT, the high cost of biodegradable materials, and the poor functionalization. The invention aims to develop a preparation technology of a multifunctional low-cost PBAT foaming modified material, which utilizes low-cost polyhydroxy sugars to react with functional groups, and uses chain extenders, compatibilizers, functional additives, etc. to carry out chain extension functionalization reaction with PBAT, thereby achieving cost reduction and melting increase of PBAT, and also giving it certain functional effects, such as antibacterial, barrier, adsorption, etc. The ratio is adjustable between 2 and 30 times, and the opening and closing pores are adjustable, thereby promoting the application of biodegradable materials in the fields of food preservation, electronic packaging, medical treatment, shoe materials, etc.

[0006] The preparation technology of the foaming material of the present invention is as follows:

[0007] 1. Mix polyhydroxy sugar, functionalized polymer group donor, catalyst and chain extender in a certain proportion and react them in a polycondensation reactor to obtain a prepolymer, and then freeze-dry to obtain hydrophobic esterified polyhydroxy sugar I;

[0008] 2. The modified polyhydroxy sugar I obtained in step 1 is processed in a certain proportion with PBAT, a chain extender, a compatibilizer, and a functional additive through a screw device to obtain a functionalized low-cost expandable PBAT modified material II or a PBAT modified foam III;

[0009] 3. The functionalized low-cost expandable PBAT modified material II prepared in step 2 is subjected to supercritical gas foaming to obtain a functionalized low-cost PBAT foam material IV.

[0010] The polyhydroxy sugar in step 1 is a natural sugar polymer containing 2 or more hydroxyl group monomers, such as one or more combinations of corn starch, sweet potato starch, wood fiber, bamboo fiber, etc.;

[0011] The functionalized polymer group donor described in step 1 is one or a blend of two or more multifunctional substances with active groups such as carboxyl, acetyl, and hydroxyl groups, such as glycolide, lactide, low molecular weight polylactic acid, low molecular weight polyglycolic acid, glycolic acid, acetic anhydride, maleic anhydride, polyacid, PPC, etc., and the molar ratio of the donor to the hydroxyl group of the polyhydroxy sugar is 1:1~2;

[0012] Step 1: The catalyst is tetrabutyl titanate, zinc acetate, zinc oxide, stannous chloride, stannous octoate, phosphoric acid, antimony trioxide, imidazoles, DMAP, ferric alcohol, etc., which are commonly used catalysts for esterification polycondensation or ring-opening polymerization, and accounts for 1% to 5% of the total mass of the polyhydroxy sugar and the functionalized polymer group donor;

[0013] In the above steps, the chain extender is a substance with multiple epoxy groups, such as BASF's ADR chain extender, Alliance Chemical's LM-S322, epoxidized soybean oil, etc., which accounts for 0.1% to 5% of the total mass of the reaction in step 1 and step 2;

[0014] In step 2, the compatibilizer, such as glycerol, ethylene glycol, aluminates, maleic anhydride grafts, etc., accounts for 0% to 10% of the total mass of the resin, and is added according to the amount of the functionalized additive in step 2;

[0015] The functional additives in step 2, such as deodorants, antibacterial agents, hardeners, antistatic agents, antioxidants, etc., are added in an amount of 1% to 30% of the total resin.

[0016] The screw processing equipment in step 2 is an injection molding machine, a twin-screw extruder, an injection molding foaming machine, an extrusion foaming machine, etc.

[0017] In step 2, the functionalized low-cost PBAT modified material II and foam III can be in the form of particles, plates, rods, and profiles;

[0018] In step 2, the supercritical gas is one of supercritical carbon dioxide and nitrogen or a blend of the two; the supercritical gas foaming device is a bead foaming or a compression foaming method.

[0019] The esterification of the polyhydroxy sugar in the present invention greatly increases its compatibility with the PBAT blending system and also expands the processing application field of biodegradable materials. The mass ratio of the esterified polyhydroxy sugar to PBAT is 1:10-1:1, preferably 1:3-1:5. Adding too much or too little esterified polyhydroxy sugar cannot guarantee the performance of the foam material.

[0020] The present invention adds a functionalized polymer group donor during the esterification process of polyhydroxy sugars, which greatly increases the strength of the foaming system and the buffering energy absorption effect, wherein the molar ratio of the functionalized polymer group donor to the hydroxyl group of the polyhydroxy sugar is 1:1-2. The above molar ratio range is an important parameter to ensure the foaming conditions. If the content of the functionalized polymer group donor is too low or too high, the strength and buffering energy absorption effect of the foam material cannot meet the requirements.

[0021] Preferably, the functionalized polymeric group donor is low molecular weight polylactic acid or PPC.

[0022] Beneficial Effects

[0023] 1. The ingredients are completely biodegradable; 2. After esterification, polyhydroxy sugars have hydrophobic and lipophilic properties and are well compatible with PBAT. In addition to increasing the amount of TPS added, it also expands the scope of application of the foaming material processing technology. For example, the existing EPP bead foaming equipment with water as the medium can be used to reduce costs while facilitating more special-shaped designs; 3. The introduction of functional groups into the polyhydroxy sugar structure can give the material barrier, biocompatibility, puncture resistance and other properties, thereby achieving partial functionalization. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Attached Figure 1 The PBAT foam formed by bead foaming in Example 1.

[0025] Attached Figure 2 Compression molded PBAT foam.

[0026] Attached Figure 3 PBAT foam film material formed by extrusion foaming.

[0027] Attached Figure 4 Comparative Example 1 PBAT bead foam particle morphology.

[0028] Attached Figure 5a Comparative Example 2: Front view of PBAT foaming.

[0029] Attached Figure 5b Comparative Example 2: Side view of PBAT foaming.

[0030] Attached Figure 6 Strain-stress compression curves of the products in Example 1 and Comparative Example 3.

[0031] Attached Figure 7 Stress-buffering coefficient curves of the bead-molded PBAT foam in Example 1 and Comparative Example 3.

[0032] Attached Figure 8 Infrared spectra of wood fiber before and after esterification in Example 2. DETAILED DESCRIPTION

[0033] It should be understood that the above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention. Example 1

[0034] Amylopectin starch, maleic anhydride, low molecular weight polylactic acid (Mn≤50000), stannous octoate, chain extender LM322, and epoxidized soybean oil were blended in a mass ratio of 75:15:10:5:1:5 and then melt-polymerized at 150-160°C for 1-2 hours in a polycondensation reactor to obtain a prepolymer, which was then freeze-dried to obtain a hydrophobic esterified starch.

[0035] The obtained hydrophobic esterified starch was blended with PBAT, hardener calcium carbonate treated with silane coupling agent, LM322, and antioxidant 1010 in a ratio of 20:60:20:0.5:0.2 and then added into a twin-screw extruder at an extrusion temperature of 150-170°C and a rotation speed of 200 rpm. Underwater granulation was performed to obtain a functionalized, low-cost, expandable PBAT modified material.

[0036] The obtained PBAT modified material was foamed in an EPP foaming kettle at 90°C and 6MPa of carbon dioxide for 1h, and then steam-formed (mold gap 15mm, pressure 0.5~0.7bar, forming and heat preservation 10~15S) to obtain a high-strength and lightweight PBAT special-shaped packaging material, see attached Figure 1 ; Example 2

[0037] Lignocellulose, acetic anhydride, PPC, zinc acetate, tetrabutyl titanate, and epichlorohydrin are mixed in a mass ratio of 70:10:20:5:1 for reaction at a reaction temperature of 160-180° C. to obtain a prepolymer, which is then freeze-dried to obtain hydrophobic esterified lignocellulose.

[0038] The obtained esterified wood cellulose was mixed with PBAT, deodorant, ADR4370, antioxidant 1010 and antibacterial agent ZnO in a ratio of 20:80:5:0.9:0.2:2 and then added into a twin-screw extruder at an extrusion temperature of 150-180°C and a rotation speed of 250rpm to obtain a 5-6mm thick functionalized low-cost expandable PBAT modified sheet.

[0039] The obtained PBAT modified sheet is placed in a molded foaming kettle, and foamed at 100-120°C with a mixture of carbon dioxide and N2 at 12-20 MPa for 2 hours to obtain a high-elastic PBAT foam for skin-friendly shoes, as shown in the attached Figure 2 ; Example 3

[0040] Starch, PPC, lactide, antimony trioxide, stannous chloride, and ADR4468 were mixed and reacted in a mass ratio of 75:10:10:2:2:1 at a reaction temperature of 160-180° C. to obtain a prepolymer, which was then freeze-dried to obtain a hydrophobic esterified starch.

[0041] The obtained esterified starch was mixed with PBAT, silicone deodorizing masterbatch, ADR4468, antioxidant 1010, and polyvalent salt polymer antibacterial agent in a ratio of 30:70:5:5:0.2:5, and then added into a supercritical nitrogen foaming twin-screw extruder at an extrusion temperature of 150-180°C, a rotation speed of 250rpm, and a pressure of 10MPa to obtain a low-cost antibacterial PBAT foaming film material with an open-pore structure, which can be used for food or medical and sanitary consumables, see attached Figure 3 .

[0042] Comparative Example 1

[0043] Comparative Example 1, directly using non-esterified starch instead of esterified starch to perform the same operation, the structure found that the foam cells in the EPP bead foaming kettle collapsed severely, the surface was sticky, and the subsequent steam molding could not be performed, see attached Figure 4 ;

[0044] Comparative Example 2

[0045] Comparative Example 2, the same operation was performed by directly using non-esterified lignocellulose instead of esterified lignocellulose. In the later foaming process, it was found that the pores collapsed, the bubble stratification was serious, and the high-rate welding was poor. See the attached Figure 5a and Figure 5b .

[0046] Comparative Example 3

[0047] Comparative Example 1, in step 1, no low molecular weight polylactic acid functional group donor is added, and the rest is consistent with Example 1.

[0048] Comparative Example 4

[0049] Comparative Example 2, no PPC functional group donor is added in step 1, and the rest is the same as Example 2.

[0050] 1 Starch color test: dissolve the esterified starch in water, add iodine solution, and observe the esterification of the starch based on the color.

[0051] 2 Infrared testing of the wood fiber before and after esterification in Example 2:

[0052] 3 Determination of expansion ratio: According to standard ISO 845-2006, the density before and after foaming is measured by the water displacement method. The expansion ratio is the ratio of the resin density before foaming to the foam density.

[0053] 4 Mechanical properties test: The PBAT foams in Example 2 and Example 3 were tested using a universal testing machine:

[0054] The compression performance of the bead-molded high-strength and lightweight PBAT special-shaped packaging foam in Example 1 was tested according to GB / T4857.4-2008, and the compression and cushioning performance of the material were tested at a compression speed of 12 mm / min. The cushioning coefficient was obtained according to the compression curve by the following formula:

[0055]

[0056] For the skin-friendly high-elastic PBAT foam for shoes in Example 2, the PBAT foam is subjected to the corresponding standards of tensile test ISO 1798-2008, compression set test GB / T6669-2008 (50°C / 50% / 6h / 30min), and right-angle tear test ISO8067-2008.

[0057] 5. Drop ball test

[0058] According to the standard GB / T6370-2008, multiple tests were conducted on the foam material and the average value was taken.

[0059] 6Hardness test

[0060] According to standard HG / T2489-2007, the foam material was tested using a Shore C hardness tester.

[0061] The esterified starch in Example 1 was tested for color reaction and found that when iodine solution was added, it did not show blue, but purple, indicating that most of the hydroxyl groups in the starch had reacted with maleic anhydride to form esters. Figure 8 In the infrared spectrum of wood fiber, 1750cm -1 Nearby C=O carbonyl peak, 1250cm -1 The enhancement and increase of the CO peak near 3400 cm -1 The reduction of the OH peak near 10 indicates that starch and wood fiber have been successfully esterified and have hydrophobic properties. Figure 1 ) and Comparative Example 1 (Appendix Figure 4 )、Example 2 (Attached Figure 2 ) and the foaming morphology of comparative example 2 (Figure 5), it can be seen that the esterification of polyhydroxy sugars greatly increases its compatibility with the PBAT blending system, and also expands the processing application field of biodegradable materials, greatly reducing the promotion cost.

[0062] From the attached Figure 6 The compression curve strain-stress curve of Example 1 and Comparative Example 3 and the attached Figure 7 According to the attached Figure 6It can be seen from the stress-buffering coefficient C curves of Example 1 and Comparative Example 3 that the strength of the foam materials (the greater the Young's modulus, the greater the strength) is in the order of Example 1>EPS>Comparative Example 3. The results of the buffering coefficient also show a similar pattern, indicating that the addition of crystalline low molecular weight polylactic acid greatly increases the strength of the foaming system and the buffering energy absorption effect, which is also greatly improved compared with the competing EPS.

[0063] From the comparison of the PBAT foam product performance lists of Example 2 and Comparative Example 4 in Table 1, it can be seen that the addition of PPC has little effect on the foaming ratio, but greatly improves the tensile, rebound, tearing and other performances of the foaming material, and the toughening and strengthening effects are detailed. When used in shoe materials, the durability of the material is greatly improved. Combined with the synergy of antibacterial and deodorizing functional additives, it will greatly promote the application of PBAT materials in high-end shoe materials, medical and sanitary consumables and other fields.

[0064] Table 1 PBAT foam product performance of Example 2 and Comparative Example 4

[0065]

Claims

1. A method for preparing a PBAT foaming modified material, characterized in that: The method comprises the following steps: (1) A polyhydroxy sugar, a functionalized polymer group donor, a catalyst, and a chain extender are mixed in a certain proportion and reacted in a polycondensation reactor to obtain a prepolymer, and then freeze-dried to obtain a hydrophobic esterified polyhydroxy sugar I; wherein the functionalized polymer group donor is selected from a mixture of maleic anhydride and low molecular weight polylactic acid with a Mn of ≤50,000 in a mass ratio of 15:10 or a mixture of PPC and lactide in a mass ratio of 10:10, and the molar ratio of the functionalized polymer group donor to the polyhydroxy sugar hydroxyl group is 1:1-2; (2) the modified hydrophobic esterified polyhydroxy sugar I obtained in step (1) is processed in a certain proportion with PBAT, a chain extender, a compatibilizer, and a functional additive through a screw device to obtain a functionalized low-cost expandable PBAT modified material II or a PBAT modified foam III; (3) subjecting the functionalized low-cost expandable PBAT modified material II obtained in step (2) to supercritical gas foaming to obtain a functionalized low-cost PBAT foam material; Adding functionalized polymer group donors during the esterification process of polyhydroxy sugars increases the strength of the foaming system and the buffering energy absorption effect; The esterification of polyhydroxy sugars increases the compatibility of polyhydroxy sugars and PBAT blending systems.

2. The method for preparing a PBAT foaming modified material according to claim 1, characterized in that : The polyhydroxy sugar described in step 1 is a natural sugar polymer containing monomers with more than two hydroxyl groups.

3. The method for preparing a PBAT foaming modified material according to claim 2, characterized in that The natural carbohydrate polymer is one or a combination of corn starch, sweet potato starch, wood fiber and bamboo fiber.

4. The method for preparing a PBAT foaming modified material according to claim 1, characterized in that The catalyst in step 1 is tetrabutyl titanate, zinc acetate, zinc oxide, stannous chloride, stannous octoate, phosphoric acid, antimony trioxide, imidazoles, DMAP or ferric alcohol, which accounts for 1% to 5% of the total mass of the polyhydroxy sugar and the functionalized polymer group donor.

5. The method for preparing a PBAT foaming modified material according to claim 1, characterized in that : The compatibilizer in step 2 is glycerol, ethylene glycol, aluminate or maleic anhydride graft, accounting for 0% to 10% of the total mass of the resin; the functionalized auxiliary agent in step 2 is a deodorant, antibacterial agent, hardener, antistatic agent or antioxidant, and the added amount accounts for 1% to 30% of the total mass of the resin.

6. The method for preparing a PBAT foaming modified material according to claim 1, characterized in that : In step 2, the PBAT modified material II and foam III are in the shape of particles, plates, rods or profiles.

7. The method for preparing a PBAT foaming modified material according to claim 1, characterized in that : In step 2, the supercritical gas is one of supercritical carbon dioxide and nitrogen or a blend of the two; the supercritical gas foaming device is bead foaming or molded foaming.

Citation Information

Patent Citations

  • Full-biodegradable modified PBAT foamed sheet, and preparation method and application thereof

    CN113549305A

  • Hydrophobic thermoplastic starch composite and method for manufacturing the same

    US20200048436A1

Cited By

  • PBAT / EVA composite foam material based on chemical grafting modification and preparation method thereof

    CN122302349A